2019
DOI: 10.3928/1081597x-20190417-02
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Outcomes and Patient Satisfaction After Bilateral Implantation of an EDOF IOL and a Mix-and-Match Approach

Abstract: PURPOSE: To evaluate visual outcomes at different distances (near, intermediate, and far), depth of focus, optical quality, quantitative dysphotopsia, and patient satisfaction in two groups. METHODS: The extended depth of focus (EDOF) only group (n = 40 eyes) was implanted bilaterally with an EDOF intraocular lens (IOL) and the mixed group (n = 40 eyes) was implanted with the same EDOF IOL in the dominant eye and a trifocal IOL in the fellow eye. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 22 publications
3
25
1
2
Order By: Relevance
“…In another published study where the target was emmetropia in both eyes, 94% reported minimal or no photic phenomena at 4–6 months postop with a median satisfaction score of 9/10 for distance vision and near and 10/10 for intermediate vision 10. A study of the same lens by Tarib et al noted that halos and glare were observed by 70% and 30% of the patients, respectively 11. Mean VA has also been reported in the literature.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In another published study where the target was emmetropia in both eyes, 94% reported minimal or no photic phenomena at 4–6 months postop with a median satisfaction score of 9/10 for distance vision and near and 10/10 for intermediate vision 10. A study of the same lens by Tarib et al noted that halos and glare were observed by 70% and 30% of the patients, respectively 11. Mean VA has also been reported in the literature.…”
Section: Introductionmentioning
confidence: 75%
“…Mean VA has also been reported in the literature. Uncorrected distance visual acuity (UDVA) ranged from −0.0411 to 0.08 logMAR12 with a target of emmetropia. Distance-corrected intermediate VA (DCIVA) was 0.19 logMAR12 and the best distance-corrected near VA (DCNVA) ranged from 0.3211 to 0.33 logMAR 12…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Mix-and-match of IOLs with different add powers is an approach that has been used to individualize visual correction. [11][12][13] Combinations of near add MIOLs and low add MIOLs, such as +4.0 D add and +2.75 D IOLs have shown good visual acuities for near and distance performance, however less has been reported about the combination of +2.75 D with a +3.25 D IOL. 14,15 Patients with unique lifestyle needs can now choose to combine IOL options to best suit their visual needs.…”
Section: Introductionmentioning
confidence: 99%
“…Auch hier werden, wenn auch optikbedingt in deutlich geringerem Ausmaß als bei refraktiven Optiken, die Vorteile der MIOL mit geringeren Halo-und Glare-Phänomenen bei diesmal geringerem Nahzusatz kombiniert. Wir verwenden diese Technik durch die Kombination der EDOF-Linse LARA 829MP im fernkorrigierten Auge und der trifokalen LISA 839MP im nahkorrigierten Auge [53] (vgl. ▶ Abb.…”
Section: And Match Blended Vision üBerblendvisusunclassified